The Achilles’ heel of positivism - D.F.M. Strauss (Koers : Bulletin for Christian Scholarship, 2003)
The 20th century encompasses philosophical trends as wide apart as (neo-) positivism and postmodernism. The assumed objectivity and neutrality of the former and the radical relativity claimed by the latter both have difficulties in accounting for the nature of universality. Since sense experience is directed towards concrete entities and events, the universal scope of law-statements remains problematic – particularly exemplified in the universal scope of modal terms (what will be designated as modal universality). Not even postmodernism can side-step this fundamental ontic dimension of reality. Insofar as the positivistic ideal of an objective and neutral science still dominates the thought-world of many practising (natural and social) scientists, a critique of the Achilles’ heel of positivism may render a service to the ideal of Christian scholarship, since it is argued that such a critique highlights the inevitability of a distinct theoretical view of reality which ultimately emanates from a person’s deepest convictions. The contributions of Popper and Stegmüller are contextualized in the argumentation. Popper realized that rationality needs a more-than-rational foundation and Stegmüller acknowledges that one cannot justify something without a prior trust. The inability of sense experience to account for the functional properties of natural things and their accompanying concepts indeed reveals the Achilles’ heel of positivism. This view is explained with reference to the uniqueness of function concepts employed in the historical development of the concept of matter. In the final part of the article Popper’s idea of falsification is assessed by taking into account the criticism raised by Stegmüller. In the course of the argumentation the relevance for the South African context is mentioned with reference to the idea of neutrality as it is advanced in the current debate about the teaching of religion at school.